Analysis of Syntactic Material in the Textbook of SDN 03 Cemaka Putih Class 1-3 - Agustin, Arni Fitriani Dwi; Fadhilah, Muhammad Yaasiin; Nuryani, Nuryani (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
This research is entitled "Analysis of Syntactic Material in Textbook Material at SDN 03 Cempaka Putih Grades 1-3." Many people do not know that syntactic material has also been studied since elementary school, therefore the researcher decided to conduct this research. The purpose of this research is to find out what material is related to syntax in class 1-3 textbooks at SDN 03 Cempaka Putih. This type of research is descriptive qualitative. The data collection technique was carried out through observation by borrowing textbooks from grade 1-3 teachers at SDN 03 Cempaka Putih and carrying out reading, listening and note-taking techniques. The subject of this study is the syntactic material contained in the textbooks used at SDN 03 Cempaka Putih grades 1-3. The results showed that of the 17 textbooks used at SDN 03 Cempaka Putih grades 1-3, there were 9 materials related to syntax. The material found in the textbooks used at SDN 03 Cempaka Putih grades 1-3, namely words and sentences.